2015
DOI: 10.1136/bmj.h568
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between traumatic tap and aneurysmal subarachnoid hemorrhage: prospective cohort study

Abstract: Objectives To describe the findings in cerebrospinal fluid from patients with acute headache that could distinguish subarachnoid hemorrhage from the effects of a traumatic lumbar puncture. Design A substudy of a prospective multicenter cohort study. Setting 12 Canadian academic emergency departments, from November 2000 to December 2009. Participants Alert patients aged over 15 with an acute non-traumatic headache who underwent l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 30 publications
1
61
1
3
Order By: Relevance
“…Perry et al 9 enrolled 1739 awake patients older than 15 years who had severe headaches. They concluded that a sensitive cutoff point for RBC counts in SAH was more than 2000 310 6 /L.…”
Section: Resultsmentioning
confidence: 99%
“…Perry et al 9 enrolled 1739 awake patients older than 15 years who had severe headaches. They concluded that a sensitive cutoff point for RBC counts in SAH was more than 2000 310 6 /L.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, for practical purposes, we assumed that the lowest RBC count represented the last tube collected in all cases, consistent with the definition used in the derivation study of interest [11].…”
Section: Methods and Measurementsmentioning
confidence: 99%
“…Recently, data from the largest prospective study examining diagnostic testing for SAH revealed that, among 1739 patients undergoing LP, the presence of either a CSF RBC count 2000 × 10 6 /L or more or visible xanthochromia identified 15 patients with aSAH with 100% sensitivity (95% confidence interval [CI], 74.7-100.0) [11]. Given this potentially promising approach, we sought to provide a narrower CI for sensitivity by applying these CSF analysis criteria to a 13-year case series of patients diagnosed with aSAH after LP.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations